Prognosis of patients with prolonged disorders of consciousness after brain injury: a longitudinal cohort study - Yan, Dong; Simei, Liu; Hongzhao, Bai; Hongyan, Du; Yuchao, Ding (Frontiers in Public Health, 2024)
The findings regarding the prognosis of prolonged disorders of consciousness(PDOC) vary widely among different studies. This study aims to investigate the mortality, consciousness recovery and disabilities of patients with PDOC after brain injury.Methods: A total of 204 patients with PDOC were included in a longitudinal cohort study, including 129 males and 75 females. There were 112 cases of traumatic brain injury(TBI), 62 cases of cerebral hemorrhage(CH), 13 cases of cerebral infarction(CI) and 17 cases of ischemic hypoxic encephalopathy(IHE). The status of consciousness at 1, 2, 3, 6, 12, 18, 24, 36, 48 months of the disease course was assessed or followed up using the Revised Coma Recovery Scale(CRS-R). If the patients were conscious, the disability Rating Scale(DRS) was also performed. The prognosis of different PDOC including coma, vegetative state(VS) and minimal conscious state(MCS) was analyzed. The survival patients were screened for variables and included in multivariate binary Logistic regression to screen the factors affecting the recovery of consciousness.The mortality rates at 12, 24, 36 and 48 months were 10.7%, 23.4%, 38.9% and 68.4%, respectively. The median time of death was 18 months(8.75, 29). The probability of MCS regaining consciousness was higher than VS(P<0.05), with the degree of disability left lower than VS(P<0.05). There was no significant difference between MCS-and MCS+ groups in terms of the probability of regaining consciousness, the extent of residual disability, and mortality rates(P>0.05). The mortality rate of coma was higher than that of other PDOC(P<0.05). The mortality rate of MCS was lower than that of VS, but the difference was not statistically significant(P>0.05). The probability of consciousness recovery after TBI was the highest and the mortality rate was the lowest. The possibility of consciousness recovery in IHE was the least, and the mortality rate of CI was the highest. The cause of brain injury and initial CRS-R score were the factors affecting the consciousness recovery of patients(P<0.05).The prognosis of MCS is more favorable than VS, with comparable outcomes between MCS-and MCS+, while comatose patients was the poorest. TBI has the best prognosis and IHE has the worst prognosis.